Improved on-off algorithm for adaptive antenna arrays in CDMA mobile communication systems - Ghanem, K.; Denidni, T.A. (2003 IEEE Topical Conference on Wireless Communication Technology : October 15-17, 2003, Honolulu, HI, 2003)
The conventional generalized on-off algorithm (Choi et al. (2002)) requires many bit durations to converge. In order to reduce the processing time, a new algorithm, called the variable on-off (VOO), is proposed. This algorithm carries out the updating for chip duration instead of the bit duration, and performs the adaptation for the different paths at the same time. The latter operation allows us to reduce the processing time by L, where L is the number of paths. When the channel is subject to rapid variations or under high mobility, the angles of arrival change significantly over some symbol intervals. To overcome these problems, the variable step size of the VOO algorithm, which follows power gradient variation, allows the tracking of such an adverse environment, while simultaneously tracking the maximum power.